Incidence and Risk Factors for Postoperative Complications of Rectovaginal Fistula Repairs, Based on Different Surgical Routes. Issue 1 (January 2021) - Chong, Woojin; Liu, Tracey; Bui, Anthony
Abstract : Objective: To investigate incidence and risk factors for postoperative complications after rectovaginal fistula (RVF) repairs, based on different surgical routes. Methods: This retrospective cohort study utilized CPT codes to identify RVF repairs performed during 2005 to 2017 from the American College of Surgeons National Surgical Quality Improvement Program database. Demographic/clinical characteristics were compared among different surgical routes. Logistic regression was performed to identify associations. Results: Among 1398 RVF cases, 1391 were included for final analysis: 159 (11.4%) were performed transabdominally (group 1), 253 (18.2%) transperineally (group 2), and 979 (70.4%) transvaginally/transanally (group 3). Group 1 was older compared with groups 2 and 3 (58.72 ± 15.23 years vs 44.11 ± 13.51 years vs 46.23 ± 14.31 years, P < 0.0001). Race/ethnicity was comparable in all groups with non–Hispanic-White most common. Comparably, group 1 had higher preoperative comorbidities: hypertension requiring medication ( P < 0.0001), chronic obstructive pulmonary disease (COPD) ( P = 0.0347), preoperative infection ( P = 0.002), functional dependence ( P = 0.0001), and longer time between hospital admission to operation ( P < 0.0001). Group 1 also had longer operating time ( P < 0.0001); more American Society of Anesthesiologist ≥ 3 classification ( P < 0.0001); and more likely inpatient status ( P < 0.0001). The overall incidence of any postoperative complications was 13.2% (25.2%, group 1 vs 15.8%, group 2 vs 10.6%, group 3; P < 0.0001). The most common postoperative complications included unplanned readmission, postoperative superficial surgical site infection, and reoperation. The incidence of severe postoperative complications was 7.9% (17%, group 1 vs 7.1%, group 2 vs 6.6%, group 3, P < 0.0001): group 1 had highest rates of pulmonary embolism ( P = 0.0004), deep venous thrombosis ( P = 0.0453), bleeding requiring transfusion ( P < 0.0001), stroke ( P = 0.0207), unplanned reintubation ( P = 0.0052), and death ( P = 0.0004). Group 1 also had highest rates of minor postoperative complications like urinary tract infection ( P = 0.0151), superficial surgical site infection (P = 0.0189), and pneumonia ( P = 0.0103). In addition, group 1 had the greatest postoperative length of stay ( P < 0.0001). In multivariate analysis, age ( P = 0.0096), inpatient status at the time of surgery ( P = 0.0004), and operating time >2 to 3 hours ( P = 0.0023) were significant predictors of postoperative complications within 30 days after surgery. Conclusions: The overall incidence of complications after RVF repairs+/−concomitant procedures was 13.2%. The overall incidence of severe complications was 7.9%. The abdominal approach had more postoperative complications but it was not an independent predictor of postoperative complications after RVF repair. Abstract : Supplemental digital content is available in the text.